Mathematical Modeling of Middle East Respiratory Syndrome Coronavirus with Bifurcation Analysis - Mehmet Yavuz; Rahman, Mati ur; Yildiz, Mustafa; Joshi, Hardik (Contemporary Mathematics, 2024)
The Middle East respiratory syndrome is a viral respiratory illness. It is caused by a common type of virus called coronavirus. The main objective of the present work, we develop a mathematical model for the transmission dynamics of the Middle East respiratory syndrome coronavirus (MERS-CoV) disease. To assess the transmissibility of the MERS-CoV, we calculate the basic reproduction number R0. Furthermore, the existence of the backward bifurcation for different parameters is presented. The sensitivity analysis is presented to analyze the importance of various epidemic parameters. Stability analysis for the model is examined to provide stability conditions. Finally, we present the numerical simulations of the proposed model to support our analytical findings.